Research progress on protein translational reprogramming in tumors - FAN Ying, LIU Yang, LIU Yanyong (Jichu yixue yu linchuang)
Protein translational reprogramming is an important compensatory change made by cells in response to a variety of stimuli, resulting in rapid, specific changes to the cellular proteome. In tumor cells, this reprogramming is regulated through several mechanisms, including the internal ribosome entry site (IRES), cap-independent translational enhancers (CITE), and N6-methyladenosine (m6A) modifications. These processes play pivotal roles in controlling protein translational reprogramming, which is essential for tumorigenesis, progression, and treatment resistance. Further research into the function of protein translational reprogramming in tumors may reveal novel therapeutic targets and offer new avenues for cancer treatment.